2021
DOI: 10.14361/9783839452653
|View full text |Cite
|
Sign up to set email alerts
|

A New Science for Future

Abstract: Building on concepts from Science & Technology Studies, Simon David Hirsbrunner investigates practices and infrastructures of computer modeling and science communication in climate impact research. The book characterizes how scientists calculate future climate risks in computer models and scenarios, but also how they circulate their insights and make them accessible and comprehensible to others. By discussing elements such as infrastructures, visualizations, models, software and data, the chapters show how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…HCI and computer-supported cooperation work scholars have argued that digital cooperative work typically involves more fluid objects that do not only enable cooperation beyond boundaries of social worlds but also the negotiation of these boundaries (Bertelsen and Bødker, 2002;Lee, 2007). In the context of learning, we have also argued elsewhere (Hirsbrunner, 2021) that digital objects such as dynamic data visualizations can serve as anchoring devices enabling the discursive negotiation of complex matters of concern. Our own practice, then, showed that such objects can also be made productive for learning and reflection in the context of AI research.…”
Section: Creating Objects Of Social Contestation and Reflection For C...mentioning
confidence: 99%
See 1 more Smart Citation
“…HCI and computer-supported cooperation work scholars have argued that digital cooperative work typically involves more fluid objects that do not only enable cooperation beyond boundaries of social worlds but also the negotiation of these boundaries (Bertelsen and Bødker, 2002;Lee, 2007). In the context of learning, we have also argued elsewhere (Hirsbrunner, 2021) that digital objects such as dynamic data visualizations can serve as anchoring devices enabling the discursive negotiation of complex matters of concern. Our own practice, then, showed that such objects can also be made productive for learning and reflection in the context of AI research.…”
Section: Creating Objects Of Social Contestation and Reflection For C...mentioning
confidence: 99%
“…RDS employs a comprehensive network of (digital or analog) tools that enable discursive negotiations, the analysis of socio-technical (re-)positionings, and other ways of reflection. This may include anchoring devices (Hirsbrunner, 2021) for discursive negotiation of programming code such as Jupyter Notebooks, software versioning systems comparing different states of the technology, but also video-meeting software, (auto-)ethnographic notes and visual mapping tools. A promising direction for further research in an STS context would be to investigate whether we could actually speak of reflexivities in AI infrastructure or even of reflexive AI infrastructures.…”
Section: Conclusion: Reconsidering Reflexivity In Ai Researchmentioning
confidence: 99%